KKNT Membangun Desa dalam Perannya memfasilitasi Validasi Data Online UMKM Desa Pagarawan - Nyayu Siti Khodijah; Fitriani Fitriani; Ratna Santi; Minawati Minawati; Ririn Aquarina (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
The real role of community service that is regularly scheduled and related to direct academics is KKN (Real Work Class) activities. KKN (Real Work Lecture) activities are a form of education by providing learning experiences for students to live in the midst of society outside the campus. Activities facilitating online data validation; Micro, Small and Medium Enterprises (MSMEs) in Pagarawan Village are a form of development in the field of computers, both hardware and applications, which have made it easy for humans to complete work so that they can be more effective and efficient. This certainly can provide convenience, one of which is in terms of data collection. This activity is a data collection through a website in the form of a link Https:/data-umkm.babelprov.go.id which contains a description of registered MSMEs, for example the name of the business owner, NIK, KK number, what business was run, year of establishment, income to place of business. This data collection is directly supervised by the Office of Cooperatives and Small and Medium Enterprises of the Bangka Belitung Islands Province. The results of this activity include knowing the number of MSMEs in Pagarawan Village.